Purified T1 lipase, a novel construct of T1 lipase and methods thereoF - Raja Abdul Rahman, Raja Noor Zaliha; Saleh, Abu Bakar; Basri, Mahiran; Leow, Adam Thean Chor; Che Hussi, Che Haznie Ayu (2011)
The present invention relates to method to substitute second step affinity chromatography with ion exchange chromatography by site-directed mutagenesis at downstream region of GST sequences (H215R and G213R). This is to enable to diferentiate the isoelectric point (pI) value of GST from the pI value of matured T1 lipase. Also, by obtaining a new construct, new T1 lipase from the above methods, the new construct and T1 lipase was purified using two chromatography steps affinity and ion exchange chromatography. Thus, as mentioned above, the said method provides an advantage to limit or eliminate the second affinity chromatography step.